METAMORPHOSIS VISUALIZATION WITH AUGMENTED REALITY USING MARKER-BASED TRACKING - Bayu Bagus Kencana; Muhammad Fathur Prayudha; Budi Arifitama (Kresnamedia Publisher, 2020)
Metamorphosis is a cycle of biological animal growth. Learning Metamorphosis is a part of learning for students in schools specifically in the area of biology subjects. Unfortunately, the observing activities take time, and finding an animal specimen is limited to study the metamorphosis cycle. This research proposes an innovative solution to overcome these problems which is the implementation of augmented reality technology. The animal metamorphosis cycle process is visualized into 4-dimensional objects to improve interaction for the student on learning metamorphosis during learning sessions. The Marker-Based Tracking method is used as an approach where the location of the tracking pattern on the marker has been determined in advance as the place where the augmented reality object appears. The results of this study indicate that using a marker-based tracking method can improve students' understanding of metamorphosis.